The Impact of Peer-to-Peer Lending on Small Business Loans - Jin-Hyuk Kim; Frank Stähler (Center for Economic Studies and ifo Institute (CESifo), 2020)
We investigate the impact of peer-to-peer lending on the small business loans originated by US depository institutions that are subject to the Community Reinvestment Act. We present a model where a borrower can choose between a traditional bank and a crowdlending platform and show that the entry of crowdlending can induce a switching effect as well as a credit expansion effect. Using the staggered entry of LendingClub across states between 2009 and 2017, we find that the platform entry reduced the small business loans originated by banks, in particular, in the low- or moderate-income tracts as well as in the distressed middle-income tracts with a high poverty rate. A conservative estimate suggests that the crowdlending entry may have reduced the aggregate lending volume to small businesses.
Keywords: D26; G21; G28; 330; crowdfunding; marketplace lending; fintech; Community Reinvestment Act